The Next Frontier in Water Supply Service Delivery : An Assessment of the Performance of Water Sector Service Providers in Pourashavas in Bangladesh - Bahuguna, Aroha; Andres, Luis Alberto; Joseph, George; Huq, Mainul (World Bank, Washington, DC, 2019)
Using data from the International Benchmarking Network for Water and Sanitation Utilities, this paper on the water sector in pourashavas (municipalities) in Bangladesh provides an analysis of the trends in the water sector development over 2010–16. The main purpose of the paper is to examine the average performance of the water sector providers in the pourashavas to encourage conversation on identifying and addressing deficiencies in service performance in comparison with that in the rest of Bangladesh and the world. This analysis finds that although pourashavas perform on the lower end of the spectrum compared with the rest of Bangladesh on many indicators, the top 20 percent of the pourashavas are globally competitive on indicators of staff productivity, cost coverage, and daily per capita consumption of water.